MANTRA PETAPA ALAS PURWO: KAJIAN SEMIOTIKA RIFFATERRE - Mohammad Fawaid Al Fikry; Sunarti Mustamar; Christanto Pudjirahardjo (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2019)
Mantra (spell) is the oldest poem in oral literature used as a kind of prayer and hope to God through His creation. This research goals to describe the structure and meaning of the text found in Alas Purwo spells entitled